2014
DOI: 10.1007/s13361-014-1020-y
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Chromium(III) to Supercharge Peptides by Protonation at Low Basicity Sites

Abstract: The addition of chromium(III) nitrate to solutions of peptides with seven or more residues greatly increases the formation of doubly protonated peptides, [M+2H]2+, by electrospray ionization. The test compound heptaalanine has only one highly basic site (the N-terminal amino group) and undergoes almost exclusive single protonation using standard solvents. When Cr(III) is added to the solution, abundant [M+2H]2+ forms, which involves protonation of the peptide backbone or the C-terminus. Salts of Al(III), Mn(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(54 citation statements)
references
References 109 publications
4
50
0
Order By: Relevance
“…This is consistent with several studies suggesting that trivalent metal ions preferentially bind to acidic sites on peptides [50, 54-56, 58]. For example, in Figure 2 showing the ETD spectra of 2+, 3+, and 4+ precursors from fibrinopeptide B, only peptide fragments containing at least two acidic sites (i. e., glutamic acid or aspartic acid side chains and the C-terminal carboxylic acid group) are metallated.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with several studies suggesting that trivalent metal ions preferentially bind to acidic sites on peptides [50, 54-56, 58]. For example, in Figure 2 showing the ETD spectra of 2+, 3+, and 4+ precursors from fibrinopeptide B, only peptide fragments containing at least two acidic sites (i. e., glutamic acid or aspartic acid side chains and the C-terminal carboxylic acid group) are metallated.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously found that trivalent chromium, Cr(III), readily cationizes acidic and neutral peptides [58, 68, 69] and that during CID these Cr(III)-peptide ions undergo extensive sequence-informative fragmentation [68]. Also, Cr(III) readily binds to acidic peptides in solution [10, 70, 71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that the addition of chromium(III) nitrate, [Cr(H 2 O) 6 ](NO 3 ) 3 ·3H 2 O, to peptide solutions undergoing ESI can enhance peptide protonation . Neutral and acidic peptides that normally only produce singly protonated molecules, [M + H] + , can generate abundant doubly protonated molecules, [M + 2H] 2+ , when trivalent chromium, Cr(III), is present in the solution being electrosprayed.…”
Section: Introductionmentioning
confidence: 99%